Fruit and seed development in subtropical peach cultivars of different ripening seasons - Barbosa, Wilson; Ojima, Mário; Dall'Orto, Fernando Antonio Campo; Martins, Fernando Picarelli; Lovate, Alexandre Antonio (Pesquisa Agropecuaria Brasileira, 1993)
Fruits and seeds growth arid development of six peach (Prunus persica L. Batsch) cultivars: Fla. 7-3 (ultra-early-maturing), Tropical (very early), Jóia-l (early), Talismã (mid), Biuti (late) and Bolão (very late) were measured from bloom date through harvest season in the Jundiaí region (23°08'S), São Paulo State, Brazil. The period of duration of the stages I, II and III was determined for all cultivars. The results showed that about 98,5% of the fruit growth and development occurred during the stages I and III. During the stage II, with a duration of 10 ± 2 days, the mean fruit weight increased only one gram, indicating the effects of the auxinic substances that decrease fleshy mesocarp growth and promotes pit hardening. Twenty days before maturation, Fla. 7-3 and 'Tropical' duplicated the diameters and octuplicated the fruit weights; the other cultivars presented a lower fruit development. The integuments reached their maximum size at the end of stage II, when the embryo enhanced the development. The ultra-early and very early-maturing peach cultivars presented smaller embryos and little dry matter quantity. The Fla. 7-3 pits fissured mostly, aborting the embryos by the rupture of vascular bundles.